Recent Outbreaks of Rift Valley Fever in East Africa and the Middle East - Himeidan, Yousif E.; Kweka, Eliningaya J.; Mahgoub, Mostafa M.; El Rayah, El Amin; Ouma, Johnson O. (Frontiers in Public Health, 2014)
Rift Valley fever (RVF) is an important neglected, emerging, mosquito-borne disease with severe negative impact on human and animal health. Mosquitoes in the Aedes genus have been considered as the reservoir, as well as vectors, since their transovarially infected eggs withstand desiccation and larvae hatch when in contact with water. However, different mosquito species serve as epizootic/epidemic vectors of RVF, creating a complex epidemiologic pattern in East Africa. The recent RVF outbreaks in Somalia (2006–2007), Kenya (2006–2007), Tanzania (2007), and Sudan (2007–2008) showed extension to districts, which were not involved before. These outbreaks also demonstrated the changing epidemiology of the disease from being originally associated with livestock, to a seemingly highly virulent form infecting humans and causing considerably high-fatality rates. The amount of rainfall is considered to be the main factor initiating RVF outbreaks. The interaction between rainfall and local environment, i.e., type of soil, livestock, and human determine the space-time clustering of RVF outbreaks. Contact with animals or their products was the most dominant risk factor to transfer the infection to humans. Uncontrolled movement of livestock during an outbreak is responsible for introducing RVF to new areas. For example, the virus that caused the Saudi Arabia outbreak in 2000 was found to be the same strain that caused the 1997–98 outbreaks in East Africa. A strategy that involves active surveillance with effective case management and diagnosis for humans and identifying target areas for animal vaccination, restriction on animal movements outside the affected areas, identifying breeding sites, and targeted intensive mosquito control programs has been shown to succeed in limiting the effect of RVF outbreak and curb the spread of the disease from the onset.